2011
DOI: 10.3354/dao02287
|View full text |Cite
|
Sign up to set email alerts
|

Comparative susceptibility of two different genetic types of tilapia to Neobenedenia sp. (Monogenea)

Abstract: Two different genetic types of tilapia, Mozambique tilapia Oreochromis mossambicus (MT), and Pargo-UNAM (PU; a synthetic hybrid whose genetic composition is 50% Florida red tilapia, 25% Rocky Mountain tilapia, and 25% red variant Oreochromis niloticus), were acclimatized to salinity and exposed to seawater from the Gulf of Mexico off the port of Veracruz, Mexico. Both fish types were infected by the monogenean ectoparasite Neobenedenia sp. and were killed within 2 to 3 wk. A crude worm extract was prepared fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Kishimori et al 371 noted a specific antibody response to Neobenedenia in O . mossambicus , although Rubio‐Godoy et al 378 found that injecting purified worm extracts did not decrease Neobenedenia infection in tilapia. Ongoing research is likely to focus on management and decreasing the effects of infections on cultured fish and of control on the costs of production 386…”
Section: Parasitic Infections Of Tilapiamentioning
confidence: 99%
See 1 more Smart Citation
“…Kishimori et al 371 noted a specific antibody response to Neobenedenia in O . mossambicus , although Rubio‐Godoy et al 378 found that injecting purified worm extracts did not decrease Neobenedenia infection in tilapia. Ongoing research is likely to focus on management and decreasing the effects of infections on cultured fish and of control on the costs of production 386…”
Section: Parasitic Infections Of Tilapiamentioning
confidence: 99%
“…was reported from O. mossambicus and O. niloticus hybrids in Mexico's Atlantic coast. 378 Invasive O. mossambicus and Tilapia mariae in brackish water in Australia are parasitised by N. girellae (Hargis, 1955; M. Deveney, unpublished data; Figure 10a).…”
Section: Taxonomic Identitymentioning
confidence: 99%
“…Species of the family Capsalidae are also important parasites on tilapia cultured in seawater (Conroy & Conroy, 2008; Rubio-Godoy et al . 2011; Shinn et al ., 2015). Several authors have shown that the main helminth species affecting fish health in intensive closed-system culture are monogeneans.…”
Section: Tilapiamentioning
confidence: 99%
“…Gyrodactylus cichlidarum is widely distributed in Latin America (Brazil, Colombia, Ecuador, Honduras, Mexico, Puerto Rico) and has been detected in Nile tilapia ( Oreochromis niloticus ), blue tilapia ( O. aureus ), Mozambique tilapia ( O. mossambicus ) and hybrid red tilapia ( O. mossambicus × O. urolepis ) (Bunkley-Williams & Williams, 1994; Conroy, 2001; Jiménez, 2007; García-Vásquez et al , 2011; Lacerda et al , 2013; Salgado-Maldonado & Rubio-Godoy, 2014; Paredes-Trujillo et al , 2016a). Gyrodactylus cichlidarum is especially harmful to tilapia kept in ponds, attacking mainly the skin and fins (García-Vázquez et al , 2011; Paredes-Trujillo et al ., 2016a). Gyrodactylus niloticus has been recorded from Mexico on O. aureus, O. mossambicus and O. niloticus (Hernández-Martínez, 1992; López-Jiménez, 2001; Salgado-Maldonado et al , 2005).…”
Section: Tilapiamentioning
confidence: 99%
See 1 more Smart Citation